Momordica charantia Extract Treatment Extends the Healthy Lifespan of Aging Mice via the Bitter Taste Receptor/mTOR Pathway - Keiichi Hiramoto; Hirotaka Oikawa (Journal of Ageing and Longevity)
We live in a society where extending one’s healthy lifespan is becoming increasingly important. Momordica charantia (MC) extract contains many bioactive substances, such as vitamin D, phytosterols, glycosides, saponins, alkaloids, and triterpenes, and has various health-promoting effects, but its effect on extending a healthy lifespan is unknown. This study investigated the effects of MC extract on a healthy lifespan, focusing on bitter taste receptors and the mammalian target of rapamycin (mTOR). Male and female mice from the Institute of Cancer Research (ICR) were divided into control and MC-extract-treated groups, with the latter receiving oral doses of MC extract three times a week for two years. In aged male mice, MC extract increased the muscle mass and grip strength and prolonged the time to exhaustion. MC extract also enhanced the signaling from taste receptor type 2 member 1 (T2R1) to mTOR in muscle in both sexes, elevating the ribosomal protein S6 kinase beta-1 and ribosomal protein S6 levels. This T2R1/mTOR pathway works in protein synthesis and is important for increasing muscle mass. Conversely, the levels of eukaryotic translation initiation factor 4E-binding protein 1 and microtubule-associated protein light chain 3 decreased in both aged male and female mice after MC extract administration. These findings suggest that the administration of MC extract may extend the healthy lifespan of male mice, with bitter taste receptors and mTOR signaling playing key roles in this process.